Isolation And Heterotrophic Bacteria Antagonism Test From Estuary Of The Siak River with Different Salinity - Syaputry Lita Yanti; Feliatra Feliatra; Irwan Effendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted from July to September 2017 in Estuary of Siak River. The purpose of this research is to examine thepopulation of heterotrophic bacteria in Estuary of Siak River, and heterotrophic bacteria antagonism against pathogenic bacteria (Vibrio sp, Aeromonas sp and Pseudomonas sp). And than identified by phenotype and genotype. This research use survey method. The samples analisis were conducted at the Marine Microbiology Laboratory of Marine Science Department of Fisheries and Marine Faculty and DNA analisis conducted at the Genetic Laboratory of Biology Department Mathematic and Natural Sciences. The result of antagonism test from 25 isolate heterotrophic bacterial was found 10 isolates which have ability to inhibit the growth of pathogenic bacteria (Vibrio sp, Aeromonas sp and Pseudomonas sp). From Vibrio sp bacteria the mean of clear zone is 1P11 isolate of 20,3 mm and the smallest is 1P19 isolate of 5 mm. Aeromonas sp bacteria the largest clear zone is 2P20 of 9,3 mm and the smallest is 1P12 isolate of 3,3 mm. Pseudomonas sp bacteria the largest clear zone is 1P12 isolate of 17 mm and the smallest is 1P11 and 2P22 isolate of 8,3 mm. the result of molecular identification using PCR 16S rRNA method and BLAST analisis showed 10 isolates of heterotrophic bacteria having kinship with bacteria of the genus Bacillus that is Bacillus cereus (1P11, 1P12, 1P14, 1P15, 1P19, 2P20, 2P21, 2P23), Bacillus toyonensis (2P22) and Virgibacillus salarius (1P18). Keyword : Heterotrophic Bacteria, Isolation, Antagonism test, Identification